DEVELOPMENT OF KUTANG BEACH TOURIST OBJECT BY BUMDESA BAROKAH MAKMUR IN LABUHAN VILLAGE, BRONDONG DISTRICT, LAMONGAN REGENCY - Murod, Iqbal Nailul; Tukiman, Tukiman (DIA: Jurnal Administrasi Publik, 2021)
Kutang beach tourism object is a type of ecotourism that offers beautiful beach tourism and is equipped with various interesting photo spots which are managed and developed directly by BUMDesa Barokah Makmur, Labuhan Village, Brondong District, Lamongan Regency. The purpose of this research is to find out how the development of the Kutang beach tourism object carried out by BUMDesa Barokah Makmur. The type of this research is descriptive qualitative with data collection techniques in the form of interviews, observation, documentation, and literature study. The focus of this study is to use 4 (four) indicators of tourism destination development by Sedarmayanti. (2018), namely: Tourist attraction, attractions, facilities, and accessibility. Sources of data used are informants and documents related to research. Sampling in this study is using the purposive sampling technique. Data analysis techniques used are data collection, data condensation, data presentation, and drawing conclusions. The results of this study indicate that the development carried out by BUMDesa Barokah Makmur as a driving force of the Kutang beach tourism object has been carried out well. However, there are several obstacles in the process of developing Kutang beach tourism objects which are still lacking, including the absence of several tourist facilities or public facilities such as prayer rooms or places of worship, electric sockets in the gazebo, and a map of the location. of Kutang beach attractions.